Construction of Public Opinion about Religious Moderation on NU Online Instagram Accounts (@nuonline_id) - Soraya, Serin Himatus; Wibowo, Wahyu Tri (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2021)
This study tries to describe how NU Online constructs the content of religious moderation in influencing public opinion. Starting from the development of social media in the digital era, which plays a significant role in building public opinion and culture, NU Online uses Instagram (@nuonline_id) to spread the concept of moderation. The spread of the moderation message aims to maintain the country’s integrity and prevent radicalism or extremism in religion. This research is descriptive qualitative research. The study conducts by online observations of the @nuonline_id Instagram page to detect religious moderation content. This study succeeded in finding the construction of religious moderation on the @nuonline_id account using text analysis (images and text). The study results explain that NU Online carries out the structure of religious moderation in six aspects of life: (a) Aspects of inter-religious relations. In this aspect, NU Online invites Muslims to maintain harmony with people of different religions. (b) Aspects of social life by suggesting the Indonesian people live in harmony with each other as Indonesian citizens. (c) Political factors and state management by asking the government to develop moderation in carrying out their duties. (d) The education aspect is by the inculcation of the moderation concept in the curriculum. (e) Legal aspects and understanding of religious texts encourage Islamic scholars to consider the religious context in establishing laws. (f) Economic factors, taking into economic equity.